Household Waste Management towards a New Normal Era (Study at Suzuki Residents, Watutumou III Village, Kalawat District) - Ika Saputri Wulandari; Koderi Koderi; Soemarno Soemarno (Research Centre of Inorganic Materials and Complexs, 2021)
This research was conducted to (1) analyze the household waste management system, and (2) develop a strategy for household waste management in Suzuki Resident, Watutumou III Village, Kalawat District, getting in the era of